Biceps and Triceps Muscle Activation Under Progressive Loads: A Study on Functional Symmetry of the Upper Limbs - Haider Hashim; Saif Ali Mohammed; Bashar Mohammed Ali; Safaa A. Ismaeel; Mohammed Nasir (Biyumikānīk-i varzishī)
Objective This study aimed to assess the biomechanical aspects of neuromuscular balance in the upper limbs during closed-chain resistance training with progressively increasing loads. Specifically, it investigated how incremental load variations affect the recruitment of agonist and antagonist muscles and examined the biomechanical relationship between load intensity and muscle coordination. Methods A total of 22 healthy male participants (aged 23–26 years) with resistance training experience were included. The participants performed upper-limb exercises using a multi-gym resistance machine under a closed-chain kinetic setup. The protocol included three sets at 50%, 75%, and 90% of one-repetition maximum (1RM), each set comprising six repetitions with a 60-second rest interval. Electromyographic (EMG) data were collected using a MyoTrace 400 system, with surface electrodes placed on agonist and antagonist muscles following Noraxon placement standards. EMG signals were processed to compute root mean square (RMS) values, normalized to each participant’s maximum voluntary isometric contraction (MVIC). Statistical comparisons were performed using paired t-tests and one-way ANOVA (with Bonferroni post-hoc tests), with significance set at p < 0.05. Results EMG activity in both the biceps (agonist) and triceps (antagonist) muscles showed significant increases as the load progressed from 50% to 90% 1RM. At the highest load (90% 1RM), no statistically significant difference was observed between the right and left limb EMG amplitudes, indicating a high degree of bilateral neuromuscular symmetry. These results align with previous biomechanical studies demonstrating that progressive loading enhances motor unit recruitment and influences agonist–antagonist muscle activation patterns. Conclusion Closed-chain resistance training with incremental loading provides biomechanical evidence of enhanced upper limb muscle recruitment, contributing to improved movement stability, motor control, and neuromuscular balance. These findings highlight the importance of progressive resistance training in both athletic and rehabilitative settings for optimizing performance and reducing injury risk. Future research should further explore the effects of varying rest intervals and repetition schemes on neuromuscular adaptation to refine training guidelines.